New insights into novel inhibitors against deoxyhypusine hydroxylase from plasmodium falciparum: compounds with an iron chelating potential - Von Koschitzky, Imke; Gerhardt, Heike; Laemmerhofer, Michael; Kohout, Michal; Gehringer, Matthias; Laufer, Stefan; Pink, Mario; Schmitz-Spanke, Simone; Strube, Christina; Kaiser, Annette (Amino Acids, 2015)
Deoxyhypusine hydroxylase (DOHH) is a dinuclear iron enzyme required for hydroxylation of the aminobutyl side chain of deoxyhypusine in eukaryotic translation initiation factor 5A (eIF-5A), the second step in hypusine biosynthesis. DOHH has been recently identified in P. falciparum and P. vivax. Both enzymes have very peculiar features including E-Z type HEAT-like repeats and a diiron centre in their active site. Both proteins share only 26 % amino acid identity to the human paralogue. Hitherto, no X-ray structure exists from either enzyme. However, structural predictions based on the amino acid sequence of the active site in comparison to the human enzyme show that four conserved histidine and glutamate residues provide the coordination sites for chelating the ferrous iron ions. Recently, we showed that P. vivax DOHH is inhibited by zileuton (N-[1-(1-benzothien-2-yl)ethyl]-N-hydroxyurea), a drug that is known for inhibiting human 5-lipoygenase (5-LOX) by the complexation of ferrous iron. A novel discovery program was launched to identify inhibitors of the P. falciparum DOHH from the Malaria Box, consisting of 400 chemical compounds, which are highly active in the erythrocytic stages of Malaria infections. In a first visual selection for potential ligands of ferrous iron, three compounds from different scaffold classes namely the diazonapthyl benzimidazole MMV666023 (Malaria Box plate A, position A03), the bis-benzimidazole MMV007384 (plate A, position B08), and a 1,2,5,-oxadiazole MMV665805 (plate A, position C03) were selected and subsequently evaluated in silico for their potential to complex iron ions. As a proof of principle, a bioanalytical assay was performed and the inhibition of hypusine biosynthesis was determined by GC-MS. All tested compounds proved to be active in this assay and MMV665805 exhibited the strongest inhibitory effect. Notably, the results were in accordance with the preliminary quantum-mechanical calculations suggesting the strongest iron complexation capacity for MMV665805. This compound might be a useful tool as well as a novel lead structure for inhibitors of P. falciparum DOHH.
EVALuna2:9734